Số hóa bởi Trung tâm Học liệu – Đại học Thái Nguyên
Số hóa bởi Trung tâm Học liệu – Đại học Thái Nguyên
Số hóa bởi Trung tâm Học liệu – Đại học Thái Nguyên
Số hóa bởi Trung tâm Học liệu – Đại học Thái Nguyên
Số hóa bởi Trung tâm Học liệu – Đại học Thái Nguyên
X
X .
X
x ≥ 0, ∀x ∈ X; x = 0 ⇔ x = 0.
αx =| α | ·x, ∀α ∈ R, ∀x ∈ X.
∀x, y ∈ X, x + y ≤ x + y.
R
k
x = (x
1
, , x
k
)
y = (y
1
, , y
k
)
xy = x
1
y
1
+ x
2
y
2
+ + x
k
y
k
.
(x, y) = (y, x)
(x + y, z) = (x, z) + (y, z)
(αx, y) = α(x, y)
(x, x) ≥ 0 (x, x) = 0 ⇔ x = 0
(x, x) = x
2
(x, y)
(x + y, x + y) + (x − y, x − y) = 2(x, x) + 2(y, y).
x + y
2
+ x − y
2
= 2(x
2
+ y
2
).
Số hóa bởi Trung tâm Học liệu – Đại học Thái Nguyên
x
(x, x) X
X
α
0 ≤ (x − αy, x − αy) = (x, x) − 2α(x, y) + α
2
(y, y),
| (x, y) |≤ x . y .
(x + y)(x + y) = (x, x) + 2(x, y) + (y, y)
≤ x
2
+2 x . y + y
2
= ( x + y )
2
.
x + y ≤ x + y .
x > 0 x = 0.
x = 0 x = 0,
αx =| α | · x .
x X
R
n
p
x = (x
1
, , x
n
)
x =
n
i=1
| x
i
|
p
1
p
,
1 ≤ p ≤ +∞.
p = 2 E
n
n
Số hóa bởi Trung tâm Học liệu – Đại học Thái Nguyên
l
p
x = (x
1
, , x
n
)
x =
n
i=1
| x
i
|
p
1
p
< +∞,
p = 2
x, y
x ⊥ y (x, y) = 0
x ⊥ y y ⊥ x x ⊥ x ⇔ x = 0 0
x
x ⊥ y
1
, y
2
, , y
n
x ⊥ α
1
y
1
+ α
2
y
2
+ + α
n
y
n
.
x ⊥ y
n
, y
n
−→ y(n −→ ∞) x ⊥ y
M X M
⊥
0 x ⊥ M ⇒ x = 0
x ⊥ y x + y
2
= x
2
+ y
2
M
X x X
x = y + z y ∈ M, z ∈ M
⊥
y
M x x − y ≤ x − u, ∀u ∈ M
{e
n
} X
(e
i
, e
j
) = δ
ij
δ
ij
= 1 i = j δ
ij
= 0 i = j
e
i
= 1, ∀i
{e
n
} x ∈ X ζ
i
= (x, e
i
)
x e
i
∞
i=1
ζ
i
e
i
x {e
n
}
∞
i=1
ζ
2
≤ x
2
∞
i=1
ζ
i
e
i
(x −
∞
i=1
ζ
i
e
i
) ⊥ e
n
{e
n
} 0
x ⊥ e
n
(n = 1, 2, ) ⇒ x = 0
Số hóa bởi Trung tâm Học liệu – Đại học Thái Nguyên
{e
n
} ζ
n
= (x, e
n
)
x e
n
{e
n
}
x =
∞
i=1
ζ
i
e
i
, ∀x ∈ X
x
2
=
∞
i=1
ζ
2
i
, ∀x ∈ X
(x, y) =
∞
i=1
ζ
i
η
i
, ∀x, y ∈ X η
i
y e
i
{e
n
} X
e
n
{e
n
} X
{e
n
}
X {ξ}
n
i=1
ξ
2
i
< ∞
x ∈ X {ξ
i
}
x =
n
i=1
ξ
i
e
i
, x
2
=
∞
i=1
ξ
2
i
.
a
X
f(x) = (a, x),
f(x) X
f = a.
f(x)
X
f(x) = (a, x) a X
f = a.
Số hóa bởi Trung tâm Học liệu – Đại học Thái Nguyên
A
X f(x, y) = (Ax, y)
f(x, y) f = A
f(x, y) X
f(x, y) = (Ax, y) A
X f = A.
A X
(Ax, y)
A
∗
(Ax, y) = (x, A
∗
y).
A
∗
A A
∗
(Ax, y) a
A
∗
= A.
(A
∗
)
∗
= A.
(A + B)
∗
= A
∗
+ B
∗
, (αA)
∗
= αA
∗
.
(AB)
∗
= B
∗
A
∗
.
A x, y
(Ax, y) = (x, Ay).
A = A
∗
A
λ A A = λx
x x
A λ
A
λ
X A
λ
A A
A
A A
Số hóa bởi Trung tâm Học liệu – Đại học Thái Nguyên
A X
x ≤ K ⇒ Ax ≤ AK.
A
A X
A B
AB, BA
A A
∗
, AA
∗
, A
∗
A
A A
N
− A −→ 0
A
A
X
A
λ | λ |= A.
0
A
x ∈ X
x =
j
(x, e
j
) + z,
e
j
0 Az = 0
Ax
0
Ax =
j
(Ax, e
j
)e
j
=
j
λ
j
(x, e
j
)e
j
.
A
Số hóa bởi Trung tâm Học liệu – Đại học Thái Nguyên
X
{x
n
}
n≥0
x
X
{x
n
} x x
n
−→ x
lim
n→+∞
x
n
− x = 0.
{x
n
} x x
n
x
lim
n→+∞
w, x
n
= w, x, ∀w ∈ X.
x {x
n
}
x
{x
n
} x x.
{x
n
} x
lim
n→+∞
x
n
= x.
{x
n
} x
X
{x
n
}
n≥0
X
{x
n
}
n≥0
X
K X
x, y ∈ K λ ∈ (0, 1)
λx + (1 − λ)y ∈ K.
Số hóa bởi Trung tâm Học liệu – Đại học Thái Nguyên
K, M
X
K ∩ M := {x : x ∈ K, x ∈ M }.
αK + βM := {x = αk + βm : k ∈ K, m ∈ M}.
K ⊂ X
x ∈ K, λ ≥ 0 ⇒ λx ∈ K.
0 ∈ X K ⊂ X
K
λ
1
x + λ
2
y ∈ K, ∀x, y ∈ K, ∀λ
1
, λ
2
≥ 0.
f : X −→ R ∪ {+∞} K ⊆ X
f K
f(λx + (1 − λ)y) ≤ λf (x) + (1 − λ)f (y),
x, y ∈ K λ ∈ (0, 1).
f K
f(λx + (1 − λ)y) < λf (x) + (1 − λ)f (y),
x, y ∈ K, x = y, λ ∈ (0, 1).
f β > 0 K
f(λx + (1 − λ)y) ≤ λf (x) + (1 − λ)f (y) − β(1 − λ)λx − y
2
,
x, y ∈ K, λ ∈ (0, 1).
f K ∀α ∈ R
L
α
(f) = {x ∈ X : f (x) ≤ α}
X
λ
x
2
2
+ (1 − λ)
y
2
2
−
λx + (1 − λ)y
2
2
Số hóa bởi Trung tâm Học liệu – Đại học Thái Nguyên
= λ
x
2
2
+ (1 − λ)
y
2
2
− λ
2
x
2
2
− (1 − λ)
2
y
2
2
− λ(1 − λ) x, y
=
λ(1 − λ)
2
(x
2
+ y
2
− 2 x, y)
=
λ(1 − λ)
2
x − y
2
.
f(x) =
x
2
2
K d
K
(x)
d
K
(x) = inf
y∈K
x − y.
K d
K
x, y ∈ X λ ∈ (0, 1) z = λx + (1 − λ)y.
{x
k
}, {y
k
} K
lim
k→∞
x − x
k
= d
K
(x); lim
k→∞
y − y
k
= d
K
(y).
K z
k
:= λx
k
+ (1 − λy
k
) ∈ K
d
K
(z) ≤ z − z
k
= λ(x − x
k
) + (1 − λ)(y − y
k
)
≤ λx − x
k
+ (1 − λ)y − y
k
.
k −→ ∞
d
K
(z) ≤ λd
K
(x) + (1 − λ)d
K
(y).
π ∈ K x −π = d
K
(x) π
x K π
min
y∈K
x − y
2
2
.
π x
K K
K
N
K
(x) = {w ∈ X | w, y −x ≤ 0, ∀y ∈ K}.
π x K x − π ∈ N
K
(π)
Số hóa bởi Trung tâm Học liệu – Đại học Thái Nguyên
π x K y
K
y
λ
= λy + (1 −λ)π.
K y
λ
∈ K, ∀λ ∈ (0, 1)
x − π
2
≤ y
λ
− x
2
= (π −x) + λ(y − π)
2
.
λy − π
2
+ 2 π − x, y − π ≥ 0.
λ 0 x − π, y −π ≤ 0
y ∈ K x − π ∈ N
K
(π)
x − π ∈ N
K
(π) y ∈ K
x − y
2
= (x − π) + (π − y)
2
= x − π
2
+ π − y
2
+ 2 x − π, π −y
≥ x − π
2
+ π − y
2
≥ x − π
2
.
π x K
K x
K π π
x K y = π
x − π, π
− π ≤ 0.
π π
x − π
, π − π
≤ 0.
π −π
2
≤ 0
π = π
K X
x x K
{x
k
} K
lim
k→+∞
x
k
− x = d
K
(x).
{x
k
} {x
n
k
}
K K
K π
x − π = lim
k→+∞
x
n
k
− x = d
K
(x).
Số hóa bởi Trung tâm Học liệu – Đại học Thái Nguyên
π x K
x K
P
K
x − y
2
≥ x − P
K
(x)
2
+ y − P
K
(x)
2
, ∀y ∈ K.
f : X −→ R
f x ∈ X
f(x) ≤ lim
x
n
→x
inf f (x
n
).
f
f x ∈ X
f
(x) ∈ X
lim
y−x→0
f(y) − f (x) − f
(x), y − x
y − x
= 0.
f
(x) f x
f X X
f : X −→ R
f f
f f
lim
t→0
f(x + ty) − f(x)
t
= f
(x), y, ∀x, y ∈ X.
f x = y, x, y ∈ X
f(y) − f (x)
= y −x
f(y) − f (x) − f
(x), y − x
y − x
+ f
(x), y − x.
Số hóa bởi Trung tâm Học liệu – Đại học Thái Nguyên
lim
y−x→0
f(y) − f (x) − f
(x), y − x
y − x
= 0,
lim
y−x→0
f
(x), y − x = 0.
lim
y−x→0
(f(y) − f (x)) = 0.
f
x
t
= x + ty t > 0
f(x + ty) − f(x)
t
− f
(x), y =
f(x + ty) − f(x) − f
(x), ty
t
=
f(x
t
) − f(x) − f
(x), x
t
− x
t
=
f(x
t
) − f(x) − f
(x), x
t
− x
x
t
− x
y. (1)
lim
t→0
x
t
− x = 0,
lim
t→0
f(x
t
) − f(x) − f
(x), x
t
− x
x
t
− x
. (2)
f : X −→ R ∪{+∞} η > 0
f η
∀x, y ∈ X
f(y) − f (x) ≥ f
(x), y − x +
η
2
x − y
2
.
∀x, y ∈ X
f
(y) − f
(x), y − x ≥ ηx − y
2
.
Số hóa bởi Trung tâm Học liệu – Đại học Thái Nguyên
→
f η ∀x, y ∈ X t ∈ (0, 1)
(1 − t)f(x) + tf(y) ≥ f (ty + (1 −t)x) +
η
2
t(1 − t)x − y
2
⇒ t(f(y) − f (x)) ≥ f (ty + (1 −t)x) −f(x) +
η
2
t(1 − t)x − y
2
⇒ f(y) − f (x) ≥
f(x + t(y − x)) − f (x)
t
+
η
2
(1 − t)x − y
2
.
t −→ 0
+
f
f(y) − f (x) ≥ f
(x), y − x +
η
2
x − y
2
.
→
f t ∈ (0, 1)
z = (1 − t)x + ty.
y = z + (1 −t)(y − x)
x = z + (−t)(y − x),
f(x) ≥ f(z) + f
(z), −t(y −x) +
η
2
t
2
x − y
2
. (3)
f(y) ≥ f (z) + f
(z), (1 − t)(y − x) +
η
2
(1 − t)
2
x − y
2
. (4)
(1 − t) > 0 t > 0
(1 − t)f(x) + tf(y) ≥ f ((1 − t)x + ty) +
η
2
t(1 − t)x − y
2
.
x, y f η
→
∀x, y ∈ X
f(y) − f (x) ≥ f
(x), y − x +
η
2
x − y
2
.
f(x) − f(y) ≥ f
(y), x − y +
η
2
x − y
2
.
Số hóa bởi Trung tâm Học liệu – Đại học Thái Nguyên
0 ≥ f
(x) − f
(y), y −x+ ηx − y
2
.
→
γ(t) = f (x + th) h = x − y
γ
(t) = lim
∆
t
→0
γ(t + ∆
t
) − γ(t)
∆
t
= lim
∆
t
→0
f(x + th + ∆
t
h) − f(x + th)
∆
t
= f
(x + th), h.
f
(x + th) − f
(x), th ≥ ηth
2
= t
2
x − y
2
.
⇒ f
(x + th) − f
(x), h ≥ ηtx − y
2
.
f(y) − f (x) = γ(1) −γ(0) =
1
0
γ
(t)dt
=
1
0
f
(x + th) − f
(x), hdt
≥ F
(x), h +
1
0
ηtx − y
2
dt = f
(x), y − x +
η
2
x − y
2
.
f
f : X −→ R ∪ {+∞}
f
∀x, y
f(y) − f (x) ≥ f
(x), y − x.
∀x, y
f
(y) − f
(x), y − x ≥ 0.
Số hóa bởi Trung tâm Học liệu – Đại học Thái Nguyên
f : X −→ R K K
X
x
∗
f K
f
(x
∗
), y − x
∗
≥ 0, ∀y ∈ K.
f
f(x
∗
) f K y ∈ K
K
(1 − t)x
∗
+ ty ∈ K, ∀t ∈ (0, 1).
f((1 − t)x
∗
+ ty) = f (x
∗
+ t(y − x
∗
)) ≥ f(x
∗
).
f(x
∗
+ t(y − x
∗
)) − f(x
∗
)
t
≥ 0, ∀t ∈ (0, 1).
t 0
+
f x
∗
f(x
∗
+ t(y − x
∗
)) = f ((1 − t)x
∗
+ ty)
≤ (1 − t)f(x
∗
) + tf(y), ∀t ∈ (0, 1).
f(x
∗
+ t(y − x
∗
)) − f(x
∗
)
t
≤ f(y) − f (x
∗
), ∀t ∈ (0, 1).
t 0
+
f
(x
∗
), y − x
∗
≤ f(y) − f (x
∗
).
f(x
∗
) ≤ f(y), ∀y ∈ K x
∗
f
f x, x
f
f(
x + x
2
) ≥ f(x)
f(
x + x
2
) ≥ f(x
).
Số hóa bởi Trung tâm Học liệu – Đại học Thái Nguyên
f(
x + x
2
) ≥
f(x) + f(x
)
2
.
f(
x + x
2
) = f (
1
2
x +
1
2
x
) <
1
2
f(x) +
1
2
f(x
) =
f(x) + f(x
)
2
.
f : X −→ R ∪ {+∞} x ∈ X
w ∈ X f x
w, y −x ≤ f(y) − f(x), ∀y ∈ X.
f x ∂f (x)
∂f (x) = ∅ f x
f f
f : X −→ R ∂f (x)
x ∈ X f
K ⊂ X, f : K −→ R, K = ∅
x
∗
∈ K f K
U x
∗
f(x
∗
) ≤ f(x), ∀x ∈ K ∩ U.
x
∗
f K
f(x
∗
) ≤ f(x), ∀x ∈ K.
x
∗
f K x
∗
∈
K
0 ∈ ∂f (x
∗
).
Số hóa bởi Trung tâm Học liệu – Đại học Thái Nguyên
X
K
X K ⊆ X F : X × X −→ R ∪ {+∞}.
F K x, y ∈ K
F (x, y) + F (y, x) ≤ 0.
F K x, y ∈ K, x = y
F (x, y) + F (y, x) < 0.
F K τ > 0
x, y ∈ K
F (x, y) + F (y, x) ≤ −τx − y
2
.
F K x, y ∈ K
F (x, y) ≥ 0 ⇒ F (y, x) ≤ 0.
F K
lim
λ→0
+
sup F (λz + (1 −λ)x, y) ≤ F (x, y), ∀x, y, z ∈ K.
h : X −→ R X
F (x, y) := h(x) − h(y)
F (x, y) := h(x) − h(y) − 1
F (x, y) + F (y, x) = −2 < 0, ∀x, y ∈ X,
F τ > 0
F (x, y) + F (y, x) ≤ −τx − y
2
, ∀x, y ∈ X.
τx − y
2
≤ 2, ∀x, y ∈ X.
Số hóa bởi Trung tâm Học liệu – Đại học Thái Nguyên
x = 0 y = tm m ∈ X 0
τ ≤
2
| t | ·m
, ∀t ∈ R.
t → ∞ τ ≤ 0 τ > 0
F (x, y) := h(x) − h(y) − 1
Số hóa bởi Trung tâm Học liệu – Đại học Thái Nguyên
K
X F : K × K −→ R ∪ {+∞}
F (x, x) = 0, ∀x ∈ K
¯x ∈ K
F (¯x, y) ≥ 0, ∀y ∈ K. (EP )
F F (x, x) = 0, ∀x ∈ K
K.
F : K × K −→ R ∪ {+∞}
F (., y) y ∈ K F (x, .)
x ∈ K
K
M K
x ∈ K \ M F(x, y) < 0
(EP )
F : K × K −→ R ∪ {+∞}
F (EP )
F (., y) y ∈ K F (x, .)
x ∈ K F
(EP )
Số hóa bởi Trung tâm Học liệu – Đại học Thái Nguyên
x, y (EP ) x = y
F (x, y) ≥ 0 F (y, x) ≥ 0 F
F (x, y) + F (y, x) < 0
x ∈ K F (x, .)
µ > −∞
F (x, w) ≥ µ, ∀w ∈ B(x, 1) ∩ K.
y ∈ K \ B(x, 1) λ =
1
x − y
w = λy + (1 −λ)x ∈ B(x, 1) ∩ K.
F (x, .)
µ ≤ F (x, w) ≤
F (x, y)
x − y
.
F
F (y, x) ≤ −µx − y − τx − y
2
= −x − y(µ + τ x − y) < 0
x − y > −
µ
τ
M = K ∩ B(x, µ
),
µ
> max{1, −
µ
τ
}
n i
K
i
F
i
: K
1
× K
2
× × K
n
−→ R
n n
n
Số hóa bởi Trung tâm Học liệu – Đại học Thái Nguyên